2010
DOI: 10.1128/jb.00496-10
|View full text |Cite
|
Sign up to set email alerts
|

CztR, a LysR-Type Transcriptional Regulator Involved in Zinc Homeostasis and Oxidative Stress Defense in Caulobacter crescentus

Abstract: Caulobacter crescentus is a free-living alphaproteobacterium that has 11 predicted LysR-type transcriptional regulators (LTTRs). Previously, a C. crescentus mutant strain with a mini-Tn5lacZ transposon inserted into a gene encoding an LTTR was isolated; this mutant was sensitive to cadmium. In this work, a mutant strain with a deletion was obtained, and the role of this LTTR (called CztR here) was evaluated. The transcriptional start site of this gene was determined by primer extension analysis, and its promot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 40 publications
0
10
0
1
Order By: Relevance
“…Braz et al found that CztR autoregulates its own expression and positively regulates expression of CztA, demonstrating a link between these two proteins (51). They propose that the CztRA system is involved in zinc transport under zinc-limited conditions and that CztR may be involved in regulation of other oxidative stress genes (51). We found that a cztR mutant, but not a cztA mutant, is more susceptible to U in terms of both growth and survival, suggesting that CztR does not confer U resistance by activating expression of cztA.…”
Section: Figmentioning
confidence: 99%
See 2 more Smart Citations
“…Braz et al found that CztR autoregulates its own expression and positively regulates expression of CztA, demonstrating a link between these two proteins (51). They propose that the CztRA system is involved in zinc transport under zinc-limited conditions and that CztR may be involved in regulation of other oxidative stress genes (51). We found that a cztR mutant, but not a cztA mutant, is more susceptible to U in terms of both growth and survival, suggesting that CztR does not confer U resistance by activating expression of cztA.…”
Section: Figmentioning
confidence: 99%
“…Although the CztRA system may not be specifically induced by U, it clearly plays a role in U fitness under both survival and growth conditions. Given its previously reported function in Cd resistance (35,51), the CztRA system may be involved in a general heavy metal stress response.…”
Section: Fig 4 Transcript Levels Of Select Gene Candidates In Responsmentioning
confidence: 99%
See 1 more Smart Citation
“…Escherichia coli shows a slightly higher (1.5-fold) basal level of 8-oxodGuo in DNA than C. crescentus, but this difference is not statistically significant. Caulobacter crescentus has a myriad of regulons that promote resistance to oxidative stress (Alvarez-Martinez et al 2007;Da Silva Neto et al 2009;Lourenço and Gomes 2009;Braz et al 2010;Foreman et al 2012), and perhaps is more protected from endogenous sources of ROS, leading to lower levels of oxidative damage. Caulobacter crescentus has a myriad of regulons that promote resistance to oxidative stress (Alvarez-Martinez et al 2007;Da Silva Neto et al 2009;Lourenço and Gomes 2009;Braz et al 2010;Foreman et al 2012), and perhaps is more protected from endogenous sources of ROS, leading to lower levels of oxidative damage.…”
Section: Discussionmentioning
confidence: 99%
“…In Escherichia coli , OxyR works in concert with the small RNA oxyS to coordinate expression of catalase and peroxidase genes [3]. More recently, several other LTTRs have been shown to play a role in the oxidative stress response, including Hrg in Salmonella enterica [4], HypR in Enterococcus faecalis [5], CztR in Caulobacter crescentus [6] and HcaR in E. coli [7]. However, with the exception of OxyR, the role of LTTRs during oxidative stress remains largely uncharacterised in many bacteria.…”
Section: Introductionmentioning
confidence: 99%